The GntR/VanR transcription regulator AlkR represses AlkB2 monooxygenase expression and regulates n‐alkane degradation in Pseudomonas aeruginosa SJTD‐1 - Wanli Peng; Xiuli Wang; Qinchen Liu; Zhihong Xiao; Fulin Li; Nannan Ji; Zhuo Chen; Jiaying He; Junhao Wang; Zixin Deng; Shuangjun Lin; Rubing Liang (mLife)
Abstract Transmembrane alkane monooxygenase (AlkB)‐type monooxygenases, especially AlkB2 monooxygenases, are crucial for aerobic degradation of the medium‐to‐long‐chain n‐alkanes in hydrocarbon‐utilizing microorganisms. In this study, we identified a GntR/VanR transcription regulator AlkR of Pseudomonas aeruginosa SJTD‐1 involved in the negative regulation of AlkB2 and deciphered its nature of DNA binding and ligand release. The deletion of alkR enhanced the transcription levels of the alkB2 gene and the utilization efficiency of the medium‐to‐long‐chain n‐alkanes by strain SJTD‐1. The dimer of AlkR recognizes and binds to a conserved palindromic motif in the promoter of the alkB2 gene, and structural symmetry is vital for DNA binding and transcription repression. The long‐chain fatty acyl coenzyme A compounds can release AlkR and stimulate transcription of alkB2, reflecting the effect of alkane catabolic metabolites. Structural insights unveiled that the arginine residues and scaffold residues of AlkR are critical for DNA binding. Further bioinformatics analysis of AlkR revealed the widespread VanR–AlkB couples distributed in Pseudomonadaceae with high conservation in the sequences of functional genes and intergenic regions, highlighting a conserved regulatory pattern for n‐alkane utilization across this family. These findings demonstrate the regulatory mechanism and structural basis of GntR/VanR transcription regulators in modulating n‐alkane biodegradation and provide valuable insights in improving the bioremediation efficiency of hydrocarbon pollution.